Vibration Sensing Systems Based on Poly(Vinylidene Fluoride) and Microwave-Assisted Synthesized ZnO Star-Like Particles with Controllable Structural and Physical Properties - Chamakh, Mariem M; Mrlík, Miroslav; Leadenham, Stephen; Bažant, Pavel; Osička, Josef; AlMaadeed, Mariam Al Ali; Erturk, Alper; Kuřitka, Ivo (Nanomaterials (Basel, Switzerland), 2020)
This study deals with the effect of zinc oxide (ZnO) star-like filler addition to the poly(vinylidene fluoride) (PVDF) matrix, and its effect on the structural and physical properties and consequences to the vibration sensing performance. Microwave-assisted synthesis in open vessel setup was optimized for the preparation of the star-like shape of ZnO crystalline particles. The crystalline and star-like structure was confirmed by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDX). Furthermore, the PVDF-based composites were prepared using a spin-coating technique from solution. An investigation of the transformation of the α crystalline phase to the β crystalline phase of the neat PVDF matrix and with various filler concentrations was performed using Fourier-Transform infrared (FTIR) spectroscopy, which shows an enhanced β-phase from 44.1% to 66.4% for neat PVDF and PVDF with 10 wt.% of particles, respectively. Differential scanning calorimetry (DSC) measurements and investigation showed enhanced crystallinity and melting enthalpy of the composite systems in comparison to neat PVDF, since ZnO star-like particles act as nucleating agents. The impact of the filler content on the physical properties, such as thermal and dynamic mechanical properties, which are critical for the intended applications, were investigated as well, and showed that fabricated composites exhibit enhanced thermal stability. Because of its dynamic mechanical properties, the composites can still be utilized as flexible sensors. Finally, the vibration sensing capability was systematically investigated, and it was shown that the addition of ZnO star-like filler enhanced the value of the thickness mode d33 piezoelectric constant from 16.3 pC/N to 29.2 pC/N for neat PVDF and PVDF with 10 wt.% of ZnO star-like particles.
Keywords: structure characterization; vibration sensing; physical properties; poly(vinylidene fluoride); ZnO star-like particles